System tradeoffs in siting a solar photovoltaic material recovery infrastructure. (1st September 2015) - Goe, Michele; Gaustad, Gabrielle; Tomaszewski, Brian
Abstract: The consumption and disposal of rare and hazardous metals contained in electronics and emerging technologies such as photovoltaics increases the material complexity of the municipal waste stream. Developing effective waste policies and material recovery systems is required to inhibit landfilling of valuable and finite resources. This work developed a siting and waste infrastructure configuration model to inform the management and recovery of end-of-life photovoltaics. This model solves the siting and waste location-allocation problem for a New York State case study by combining multi-criteria decision methods with spatial tools, however this methodology is generalizable to any geographic area. For the case study, the results indicate that PV installations are spatially statistically significant (i.e., clustered). At least 9 sites, which are co-located with landfills and current MRFs, were 'highly' suitable for siting according to our criteria. After combining criteria in an average weighted sum, 86% of the study area was deemed unsuitable for siting while less than 5% is characterized as highly suitable. This method implicitly prioritized social and environmental concerns and therefore, these concerns accounted for the majority of siting decisions. As we increased the priority of economic criteria, the likelihood of siting near ecologically sensitive areas such as coastline or socially vulnerable areas such as urban centers increased. The sensitivity of infrastructure configurations to land use and waste policy are analyzed. The location allocation model results suggest current tip fees are insufficient to avoid landfilling of photovoltaics. Scenarios where tip fees were increased showed model results where facilities decide to adopt limited recycling technologies that bypass compositionally complex materials; a result with strong implications for global PV installations as well as other waste streams. We suggest a multi-pronged approach that lowers technology cost, imposes a minimum collection rate, and implements higher tip fees would encourage exhaustive material recovery for solar photovoltaic modules at end-of-life, beyond New York State. These results have important implications for policy makers and waste managers especially in locations where there is rapid adoption of renewable energy technologies. Highlights: Multi-criteria and economic models combined for spatial site suitability analysis. Sensitivity analysis revealed that criteria weighting can heavily influence siting decisions. The lowest financial cost solution is to allocate all end-of-life materials to landfill. Limited recovery begins after disposal fee increases by 40 times the current price. Exhaustive recovery requires multipronged approach that includes cheaper technology.